Post-operative Outcome of Hughes Abdominal Repair and Conventional Continuous Closure of Midline Incision in Emergency Laparotomy (Journal of Surgical Sciences, 2022)
Background: Conventional continuous closure or mass closure for abdominal closure with monofilament non- absorbable Polypropylene is one of the widely used standard techniques. Hughes repair named after Professor Leslie Hughes, is a combination of one horizontal and two vertical mattress sutures in a single suture where load is distributed along the incision length as well as across it. Objective of this study include comparing post-operative wound complications in Hughes abdominal repair and those with that by conventional continuous closure in midline abdominal incision in emergency laparotomy.Methods: This study was conducted in the Department of Surgery & Casualty, Chattogram Medical College Hospital, Bangladesh between May 2018 and April 2019. Study population included 39 patients in Group A whom Abdomen was closed by Hughes abdominal repair and 39 patients in Group B in whom Abdomen was closed by conventional continuous closure.Results: Four (10.3%) patients had wound infection in group A and six (15.4%) in group B. Two (5.1%) patients had partial wound dehiscence in group A and six (14.4%) in group B. The difference of wound infection and partial wound dehiscence were found statistically not significant. Two patients had burst abdomen in group A and nine in group B, which was found statistically significant (p